2005
DOI: 10.1111/j.1365-2966.2004.08433.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical friction on globular clusters in core-triaxial galaxies: is it a cause of massive black hole accretion?

Abstract: The present work extends and deepens previous examinations of the evolution of globular cluster orbits in elliptical galaxies, by means of numerical integrations of a wide set of orbits in five self-consistent triaxial galactic models characterized by a central core and different axial ratios. These models are valid and complete in the representation of regular orbits in elliptical galaxies. Dynamical friction is definitely shown to be an efficient cause of evolution for the globular cluster systems in ellipti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 46 publications
4
43
0
Order By: Relevance
“…The answers to these questions are of overwhelming importance to give substance to the interpretation of the formation of early-type galaxy nuclei via merging of decayed GCs, a hypothesis first raised by Tremaine et al (1975) and subsequently extensively studied by Capuzzo-Dolcetta (1993), Capuzzo-Dolcetta & Tesseri (1997), and Capuzzo-Dolcetta & Vicari (2005.…”
Section: Globular Cluster Merging and Galactic Nucleimentioning
confidence: 99%
“…The answers to these questions are of overwhelming importance to give substance to the interpretation of the formation of early-type galaxy nuclei via merging of decayed GCs, a hypothesis first raised by Tremaine et al (1975) and subsequently extensively studied by Capuzzo-Dolcetta (1993), Capuzzo-Dolcetta & Tesseri (1997), and Capuzzo-Dolcetta & Vicari (2005.…”
Section: Globular Cluster Merging and Galactic Nucleimentioning
confidence: 99%
“…Previous theoretical studies discussed the formation of stellar galactic nuclei through mergers of SCs (or GCs) in galaxies with different physical properties (e.g., Lotz et al 2001;Capuzzo-Dolcetta & Vicari 2005). Recent, fully self-consistent N -body simulations have shown that mergers of SCs in the inner regions of galaxies lead to the formation of stellar galactic nuclei with projected radial density profiles similar to what is observed (e.g., Capuzzo-Dolcetta & Miocchi 2008).…”
Section: Formation Of Stellar Galactic Nuclei Trough Sc Mergingmentioning
confidence: 88%
“…Equally, basic galactic components such as stellar galactic nuclei and thin and thick disks can also be influenced dynamically by the evolution of SC systems (e.g., Kroupa 1998;Capuzzo-Dolcetta & Vicari 2005). Radial density profiles of the stars in individual SCs formed from GMCs may depend on the strength of the tidal field of their host galaxy (e.g., Hurley & Bekki 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This difference in the density profiles has an interpretation either in terms of formation and evolution of elliptical galaxies (see [20], [17], [1], [3]). or in terms of evolution of the GCS itself (see [4], [13], [14]). The explanation on the basis of GCS evolution is more appealing, because much simpler and not based on qualitative and arbitrary modelizations of GC formation in galaxies.…”
Section: The Gcs Radial Distributions In Galaxiesmentioning
confidence: 99%